Hayek, Mill and the Liberal Tradition - Farrant, Andrew (Taylor & Francis, 2011)
"A PDF version of this book is available for free in open access via www.tandfebooks.com as well as the OAPEN Library platform, www.oapen.org. It has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license and is part of the OAPEN-UK research project. This book considers the relationship between Hayek and Mill, taking issues with Hayek's criticism of Mill and providing a broader perspective of the liberal tradition. Featuring contributions from the likes of Ross Emmett, Leon Montes and Robert Garnett, these chapters ask whether Hayek had an accurate reading of the ideas of Mill and Smith, as well as considering themes such as sympathy and analytical egalitarianism that play a large part in the liberal tradition, but less in work of Hayek These chapters argue that addition of these key ideas to the Hayekian corpus leads to a far broader understanding of the liberal tradition than that provided by Hayek "